Pemungutan Suara Ulang pada Pemihan Umum Tahun 2019 di Indonesia - Retno Sari Handayani (PERSPEKTIF, 2020)
It seems that Indonesia has not yet found the right method in implementing procedural democracy to elect legislative and executive members directly. Every election from time to time still always leaves problems. The problem to be discussed and analyzed in this study is how the application of Law Number 7 of 2017 Article 372 concerning Voting (PSU) and analyze the social problems that arise in its implementation. The research method used in this study is the normative-empirical legal research method with the live case study research category with the research category that is the legal events that the process is ongoing. As for the source of research in the form of normative legal provisions namely Law Number 7 of 2017 Article 372 as well as technical rules made with respect to these norms. The analysis shows that the implementation of the regulations made resulted in various social problems. PSU raises new problems for voters, election organizers, and election participants. A phenomenon in the form of decreased participation rates, the potential for anxiety pressure within the community because of excessive attention from officials and candidates to the distortion of preference preferences in the implementation of the PSU. The problems that arise are then expected to be considered so that the implemented PSU becomes the most appropriate solution but can still optimally minimize social problems in the community that may arise.